Case of acute mixed liver injury due to hypothyroidism. (23rd January 2018) - Duong, Nikki; Lee, Alice; Lewis, James
Abstract : The effects of hypothyroidism on the liver are not well understood. A 77-year-old woman with Hashimoto's thyroiditis had stopped taking levothyroxine on her own for 6 months. Her thyroid stimulating hormone (TSH) level was consistent with severe hypothyroidism. She resumed thyroid replacement therapy. The following month, her liver function tests were significantly elevated. Seven weeks after resumption of therapy, her TSH and liver tests had returned to normal. We attribute the mixed hepatocellular injury to hypothyroidism that resolved on correction of the hypothyroid state. This case reminds us that thyroid disease should be considered when evaluating acute liver injury.